Prediction use of helmet among motorcyclists in Perlis using structural equation modeling (SEM) - Jumatul Nuraishah Binti Saripudin (School of Environmental Engineering, University Malaysia Perlis, 2014)
The subscale factors of Theory of Planned Behaviour and Health Belief Modeltoward behaviour and intention of proper helmet use among motorcyclists in Perlis were investigated. Through this study, the relationship between construct variable and target behaviour also were determined. An interdisciplinary approach that involves behavioural sciences, injury prevention and engineering aspect all together are proved a better solution as it has the potential to enhance efforts to reduce unintentional injuries.